Toxicity abatement of wastewaters from tourism units by constructed wetlands - Calheiros, Cristina S. C. (2020)
The present research intended to investigate the toxicity abatement of domestic wastewater after passing a biosystem composed of a constructed wetland (CW) followed by a pond. The wastewater was generated in a tourism house in a rural and mountainous context and passed through a septic tank before being diverted to a CW followed by a pond. A battery of ecotoxicological tests, comprising microalgae (Raphidocelis subcapitata), macrophytes (Lemna minor), cladocerans (Daphnia magna), and bacteria (Aliivibrio fischeri), was used to assess the toxicity of the wastewater collected before and after the CW and the water of the pond. Physicochemical parameters (pH, conductivity, chemical oxygen demand, biochemical oxygen demand, total suspended solids, phosphates, ammonium, and nitrate) were also determined. The CW was able to remove carbon and nutrients from the water with a concomitant reduction of its toxicity. This study, reinforced the added value of using toxicity tests as a complement to CW operational monitoring to validate the solution and to analyze possible readjustments that may be required to improve efficiency. This study lends further support to the claim that CWs can be a sustainable solution for treating small volumes of domestic wastewater in a rural context.